Sexual dimorphism of hyoid bone - Novaković Zorica (Glasnik Antropološkog Društva Srbije, 2012)
Hyoid bone, is located in anteriorsuperior site of the neck. Represents the odd bone which is the only bone in the human body that is not articulated or otherwise normally, associated with any other bone. Bearing in mind its embryonic origin, the bone is part of the skeleton viscerocranium. It has a horseshoe shape and consists of a body, two large and two small horns. In our study, we investigated sexual dimorphism hyoid bone. Testing we did at 42 hyoid human cadaver bones with known sex and age. We made 5 oseometric mesaurements. Metric analysis of the hyoid bone is a useful technique in the determination of sexual dimorphism hyoid bone that can give good results, but is not entirely satisfactory, and can serve as a complementary method.